Implementation barriers in virtual education in Payame Noor University in Iran - AHMADI, J; NOURABADI, S (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research has been conducted with the aim of the priority of implementation barriers to virtual education at Payame Noor University. The research method is applied in terms of purpose and is descriptive in terms of data collection. The results showed that: The main barriers to implementing virtual utilization education are cultural barriers. The findings of this study indicate that: The lack of support from university administrators, lack of information and useful training for students, and lack of awareness of the higher education authorities to the virtual educational system are in the first priority of implementation barriers to providing virtual education.